Factors Causing Stunting in Toddlers - Aminuddin, Aminuddin; Arrazy, Syafran; Eliska, Eliska (Indonesian Journal of Global Health Research, 2024)
Nutritional problems in toddlers are still a major problem in the population order, one of which is stunting which is still a major nutritional problem in developing countries such as Indonesia and even still a serious global problem. The purpose of the study was to determine the factors causing stunting in toddlers in the working area of the Puskesmas Terjun, Medan Marelan District. This study used analytical survey research using a case-control design. The population of cases is mothers who have toddlers <5 years old who are stunted in the working area of the Puskesmas Waterfall Medan Marelan District, which has 23 stunting cases. Sampling is done by total sampling technique. Case and control samples were taken based on a ratio of 1: 2 with a total sample of 69 respondents. The results showed that there was a relationship between birth length (p-value 0.000), exclusive breastfeeding (p-value 0.000), maternal height (p-value 0.000), and maternal education (p-value 0.001) on the incidence of stunting. There was no relationship between birth weight (p-value 0.081) and birth distance (p-value 0.085) with the incidence of stunting in toddlers. This study concludes that there is a relationship between birth length, exclusive breastfeeding, maternal height, and maternal education with the incidence of stunting in the work area of the Puskesmas Waterfall, Medan Maryland District. It is recommended that researchers conduct further research by adding direct causal variables to enrich information about the factors that cause stunting in toddlers.